Relationship between participation in leisure activities and the maintenance of successful aging in older Chinese adults: a 4-year longitudinal study - Xiaoxiang Shen; Jin Wang; Jingwen Chen; Hongjun Zhang; Shaoshuai Shen; Xiaoguang Zhao (BMC Geriatrics, 2024)
Abstract Background It is critical to age successfully for general health considering the aging of the global population. Successful aging is an important indicator to assess whether older individuals are experiencing a healthy life and high-quality aging. This study aimed to explore the longitudinal relationship between the frequency and number of participation in leisure activities and the maintenance of successful aging. Methods This longitudinal study included a total of 1,828 Chinese adults aged 60 years or older. The following six activities were gathered to reflect leisure activities: reading books or newspapers, gardening work, playing mahjong or cards, listening to radio or watching TV, raising pets or domestic animals, and engaging in social activities. We evaluated successful aging using a multidimensional model which includes the following five components: better self-reported health, good psychological status, high cognitive function, free of disability, and better physical activity level. Results This study showed a retention rate of 58.4% for successful aging during a 4-year follow-up. Participants who frequently engaged in reading books or newspapers, gardening work, playing mahjong or cards, and listening to radio or watching TV, had higher rates of future successful aging maintenance (OR: 1.50, 95% CI: 1.04–2.22 to 1.89, 95% CI: 1.26–2.812) than those who never participated in these activities. Compared to those with 0 leisure activity, participants with 3 (OR: 1.78, 95% CI: 1.14–2.77) and 4–6 (OR: 1.65, 95% CI: 1.01–2.71) leisure activities had a greater probability of maintaining successful aging. Conclusions These findings suggest that individuals who participated more frequently in more leisure activities had a higher chance of the maintenance of successful aging in older adults. Encouraging older people to frequently participate in a greater variety of leisure activities may be an effective way to maintain successful aging over time.